INDUÇÃO DA SÍNDROME METABÓLICA EM RATOS PELO TRATAMENTO AGUDO E CRÔNICO DE DEXAMETASONA. - Vale, Bruno Nunes do; TEIXEIRA, Halbanara Louyse; JUBÉ, Jéssica Karla Borges; BERTO, Aline Matos de Carvalho; LOPES, Vinícius Gabriel Costa; OGAWA, Nelson Wataro (REVISTA CEREUS, 2016)
Introduction: Glucocorticoids are common in clinical practice, act as immunosuppressants and antiinflammatories, imitating cortisol. Despite the advantages, the inadvertent use can cause harm as desensitization to insulin, dyslipidemia, central obesity and hypertension, characterizing the metabolic syndrome. Objective: To correlate body weight, water and eating behavior, weight and ascorbic acid content (AA) of the adrenal glands and biochemical parameters of rats treated with dexamethasone (DEXA) in acute and chronic conditions. Material and Methods: Sixty Wistar rats, weighing approximately 350 g were divided into control group (GC) and DEXA groups (GD) with periods of treatment similar (24, 48, 120, 240 and 480 hours). The GC were treated with saline and GD with DEXA intraperitoneally. Data were collected from: water and food intake, body weight. Once killed, aliquots of withdrawn blood and the measured: total cholesterol, total protein and glucose, as well as adrenal weighed and measured their respective levels of AA. ANOVA followed by Tukey was used with p <0.5. Results: There was a reduction in body weight in all experimental groups even with increased fluid intake and food in all groups except in the GD-480h; was obtained atrophy of the adrenal gland in GD-240h and 480h-GD; there was depletion of AAA in GD-48h groups, GD-240h and 480h-GD; Blood glucose was increased throughout the experimental group. The lipolysis and proteolysis were observed in all experimental groups. Conclusion: The use of DEXA both short and long-term triggers profound metabolic changes, considering the criteria of the metabolic syndrome.